Non-Cash Transactions Implementation On Regional Expenditure In Improving Principles Good Governance At BPKAD East Lombok Regency - Rosmiatun Aprilia; Biana Adha Inapty; Adhitya Bayu Suryantara (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to find out how the implementation of non-cash transactions in regional spending improves the principles of good governance at BPKAD East Lombok Regency. This study uses descriptive qualitative. Data collection methods used in this study are observation, interviews and documentation. The informants from this study is a Secretary to the Agency, the Head of the Treasury, and the Spending Treasurer. The results of the study show that the implementation of non-cash transactions in regional expenditures at the BPKAD of East Lombok Regency has been going well as stipulated in the Regent Regulation No. 32 of 2018. However, the implementation of non-cash transactions at the East Lombok District BPKAD is currently not running effectively because there are still obstacles that occur, namely the lack of outreach to the community and limited infrastructure such as internet connections. With non-cash transactions in expenditure to improve the principles of good governance namely accountability, transparency, effectiveness and efficiency because areas where the flow of funds can be clearly monitored and supported by valid evidence, payments can be made quickly and accurately without having to go through intermediaries, bookkeeping can also be presented accurately and on time and can prevent fraud, especially corruption.